Pola Konsumsi Pangan, Paritas Dan Status Gizi Ibu Post Partum 4 Dan 6 Bulan Dl Kabupaten Bantul, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Breastfed mothers are included in nutritional high-risk group. At the age of 4-6 months post-partum, their weight start to decrease because of recovery and breastfeeding. Based on Susilo's research, the prevalence of inadequate food intake of pregnant mothers in Bantul regency is 28,69%. That high prevalence is caused by the lack of energy and protein intake. The nutritional status of breastfed mothers depend on their food intake during pregnancy. Nevertheless, the nutritional status of breastfed mothers aged 4-6 months who have sufficient and insufficient food intake are not known yet. The study was proposed to know the relationship between food intake pattern, the nutritional status during pregnancy, and parity with nutritional status of breastfed mothers aged 4-6 months. This study was observational using cohort combined with concurrent and noncurrent prospective study. Subjects were mothers who had baby aged 4 months. Data collected were mother's nutritional status during pregnancy, nutritional status of breasfed mothers aged 4-6 months, food intake pattern (variety, quantity, frequency, avoidance food) and social economic data (family, education, job, income, outcome and parity). Food intake was determined using FFQ. Data was analysed descriptively and analytically with chi square and logistic examination using stata program. Multivariate logistic test was used to control variable that influence nutritional status of breastfed mothers. The results showed that the most subjects, 126 (68,11%), had good food intake pattern during breastfeeding. Subjects who had 2 or more under fives was 118 subjects (63, 78%) and the average of Body Mass Index between Exposed and Non Exposed were not different. Statistic test showed that there was no relationship between food intake patterns during pregnancy with nutritional status of breastfed mothers aged 4 and 6 months. There was also no relationship between parity and nutritional status of breastfed mothers aged 4 and 6 months. Yet, there was significant influence between nutritional status during pregnancy with nutritional status of breastfed mothers aged 4 and 6 months (P